Insight into plasmonics: resurrection of modern-day science (invited) - M.A. Butt (Компьютерная оптика)
Plasmonics is a field of research and technology that focuses on the interaction between light and free electrons in a metal structure called plasmon. The study of plasmonics has gained significant attention in recent years due to its potential for several applications and its ability to manipulate light at nanoscale dimensions. Plasmonics enables the control of light at the nanoscale, far beyond the diffraction limit of conventional optics. This allows for the development of new devices and technologies with enhanced performance and functionality. In this paper, recent advances in plasmonics in medicine, agriculture, agriculture, environmental monitoring, lasers and solar energy harvesting are reviewed. Despite these promising prospects, plasmonic devices must overcome obstacles such as significant energy losses, complicated production processes, and the need for better material characteristics. Plasmonics will continue to advance because of ongoing work in nanotechnology, material science, and engineering, which will make it a more significant field with a wide range of usages in the future. In the end, the advantages and the limitations related to the realization of plasmonic devices in the real world are discussed.